Criminal and Legal Protection of the Information Security: The Experience of Foreign Legislation - RAYEV, Askhat Karimovich (Journal of Advanced Research in Law and Economics, 2017)
The problems of the information security in the context of legal regulation are studied in this article. The analytical and entity methodological approaches to the solution of this problem are substantiated. The scientific papers devoted to the problem of criminal and legal protection of the information and protection of the information security are studied. The legal regulation of the information protection in the international instruments and foreign legislation is examined. The availability in many foreign countries of the legislation, able to effectively counter the threat to the information security, is established. According to the author, in the Republic of Kazakhstan, operating in the field of protection of the information security is not that effective, due to the relatively small historical basis of development of the information technologies and the legal regulation of them. This causes the appeal to the advanced experience of the foreign countries. Special attention is paid by them to the protection of children from harmful information. The analysis of the legal regulation of the protection of the information security in the legislation of the Republic of Kazakhstan is carried out. The conclusion is made about the absence in it of the concept of the information security as a generic object of crimes, which is regarded negatively by the author. The problem of the necessity to strengthen the legal support of the information security is raised in the article. For this purpose, it is proposed to allocate it as an independent object of criminal and legal protection. According to our hypothesis, the information security can act as a primary or secondary object of encroachment. The article offers the recommendations for further improvement of the criminal legislation in this direction.